Further Contribution to the Flora of Pachmarhi Region - Kapoor, S. L.; Yadav, Hira Lal (Indian Forester, 1962)
This paper records 67 species of angiosperms as addition to the flora of the Pachmarhi region covered by Rao and Narayanaswamy, and Maheshwari In their recent publications and 25 species as new to the Pachmarhi zone of these authors; 15 species have been recorded from a new locality within the same zone. The families represented by more than 10 species are, in order of dominance: Gramineae, Papilionaceae, Cyperaceoe, Euphorbiaceae, Compositae, Acanthaceae, Scrophulariaceae, Labiatae, Amaranthaceue and Malvaceae (with equal number of species), Convolvulaceae and Tiliaceae. A quantitative analysis of the various taxa of angiosperms met with in the region is also given.